Managing Microsoft hybrid clouds : benefit from hybrid cloud scenarios through this detailed guide to Microsoft Azure Infrastructure Services (IaaS) /: benefit from hybrid cloud scenarios through this detailed guide to Microsoft Azure Infrastructure Services (IaaS). (2015) - Berg, Marcel van den
No abstract available